Comparative Evaluation of Topical 30% Metformin Cream Versus Triple Combination Cream (Kligman’s Formula) in the Treatment of Mixed Melasma - Jabeen, Saadia; Saleem, Summaya; Abid, Rabia; Tanveer, Muhammad; Falak, Asfa; Irshad, Laila (Biological and Clinical Sciences Research Journal, 2025)
Melasma is a chronic hyperpigmentation disorder characterized by irregular brown patches on sun-exposed areas of the face, causing significant cosmetic concern. The triple combination cream (Kligman’s formula) is widely used as a standard treatment but often causes irritation and other side effects. Topical metformin, known for its anti-inflammatory and antioxidant effects, has emerged as a potential alternative therapy for melasma. Objective: To compare the efficacy and safety of topical 30% metformin cream versus triple combination cream (Kligman’s formula) in the treatment of mixed melasma. Methods: This comparative study was conducted at the Department of Dermatology, CMH Gujranwala, from 1st Sep 2024 to 31st March 2025. A total of 140 patients diagnosed with mixed melasma were enrolled. Patients were assigned to receive either topical 30% metformin cream (Group A) or Kligman’s formula (Group B) applied twice daily for 12 weeks. The Melasma Area and Severity Index (MASI) score was assessed at baseline, week 4, week 8, and week 12. Adverse effects and patient satisfaction were also recorded. Results: Both groups showed a significant reduction in MASI scores over 12 weeks. The mean percentage reduction in MASI was 50.6% in the metformin group and 60.2% in the Kligman’s group (p=0.001). Adverse effects such as erythema, burning, and peeling were significantly lower in the metformin group (p<0.05). Patient satisfaction was comparable between groups. Conclusion: Topical 3% metformin cream is an effective and safer alternative to Kligman’s formula for treating mixed melasma, with fewer side effects and satisfactory results.